Oxidative stress does not influence local sweat rate during high intensity exercise - Meade, R. D.; Fujii, N.; Poirier, M. P.; Boulay, P.; Sigal, R. J.; Kenny, G. P. (Experimental Physiology, 2018)
Nitric oxide (NO)-dependent sweating is diminished during high but not moderate intensity exercise. We evaluated whether this impairment stems from increased oxidative stress during high intensity exercise. On two separate days, 11 young (24 ± 4 years) males cycled in the heat (35°C) at a moderate (500 W; 52 ± 6%VO2peak) or high (700 W; 71 ± 5%VO2peak) rate of metabolic heat production. Each session included two 30-min exercise bouts separated by a 20-min recovery. Local sweat rate was monitored at four forearm skin sites continuously perfused via intradermal microdialysis with: (1) lactated Ringer's solution (Control), (2) 10 mm ascorbate (Ascorbate; non-selective antioxidant), (3) 10 mm NG-nitro-L-arginine methyl ester (L-NAME; NO synthase inhibitor), or (4) 10 mm Ascorbate + 10 mm L-NAME (Ascorbate + L-NAME). During moderate exercise, sweat rate was attenuated at the L-NAME and Ascorbate + L-NAME sites (both ~1.0 mg·min-1·cm-2, all P < 0.05) but not at the Ascorbate site (~1.1 mg·min-1·cm-2, both P = 0.28) in comparison to the Control site (~1.1 mg·min-1·cm-2). However, no differences were observed between treatment sites (~1.4 mg·min-1·cm-2; P = 0.75) during high intensity exercise. We conclude that diminished NO-dependent sweating during intense exercise occurs independent of oxidative stress.